(untitled) (Journal of Universal Science Research, 2025)
The article examines the semantics of the zoonym Horse in phraseology on the material of German and Uzbek languages. Various phraseological dictionaries, including electronic sources, served as the material for the study. As a result, the main structural types of phraseological phrases with the component Horse were revealed, phenomena of reality, human attitude to the surrounding world were determined.